LEGAL PROBLEMS IN RESOLUTION OF GOVERNMENT ADMINISTRATIVE DISPUTES REGARDING RAPID EXAMINATION IN THE PERSPECTIVE OF LEGAL PROTECTION THEORY - Seven Putra Darius Zebua; Faisal Akbar Nasution; Mirza Nasution; Afila Afila (NOMOI Law Review, 2023)
Problematic law to inspection in a manner fast in settlement dispute administration government need studied in perspective theory protection law . Method research used _ that is juridical normative . Results study show that there is problem to inspection fast in the judicial process system business country so that For protect interest inhabitant public need done protection through approach law .